2016
DOI: 10.1073/pnas.1508535113
|View full text |Cite
|
Sign up to set email alerts
|

Gain-of-function mutations of Ptpn11 (Shp2) cause aberrant mitosis and increase susceptibility to DNA damage-induced malignancies

Abstract: Gain-of-function (GOF) mutations of protein tyrosine phosphatase nonreceptor type 11 Ptpn11 (Shp2), a protein tyrosine phosphatase implicated in multiple cell signaling pathways, are associated with childhood leukemias and solid tumors. The underlying mechanisms are not fully understood. Here, we report that Ptpn11 GOF mutations disturb mitosis and cytokinesis, causing chromosomal instability and greatly increased susceptibility to DNA damage-induced malignancies. We find that Shp2 is distributed to the kineto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 39 publications
2
25
1
Order By: Relevance
“…Subsequent analysis of E17.5 embryos confirmed that VavCre+;PTPN11 E76K embryos were dying in utero (Fig-3D). This was in contrast to recent publications that reported this model to be viable and develop MPN (Dong et al, 2016; Liu et al, 2016). This discrepancy is likely due to the use of different VavCre strains.…”
Section: Resultscontrasting
confidence: 95%
See 1 more Smart Citation
“…Subsequent analysis of E17.5 embryos confirmed that VavCre+;PTPN11 E76K embryos were dying in utero (Fig-3D). This was in contrast to recent publications that reported this model to be viable and develop MPN (Dong et al, 2016; Liu et al, 2016). This discrepancy is likely due to the use of different VavCre strains.…”
Section: Resultscontrasting
confidence: 95%
“…In contrast, non-irradiated animals expressing PTPN11 D61Y die from MPN (Chan et al, 2009a). Our findings are consistent with other studies that showed frequent T-ALL emergence in irradiated mutant PTPN11-expressing animals due to impaired DNA repair (Liu et al, 2016). As such, our results emphasize that the same mutation may give rise to divergent disease manifestations in irradiated and non-irradiated animals.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, the Shp2 enhances the Tyr phosphorylation of ER by facilitating the Src kinase activity through dephosphorylation of an inhibitory Tyr in Src kinase. Whereas the Src kinase is broadly recognized as a cytoplasmic protein, recent reports also observed the nuclear function of this kinase that was activated by Shp2 through dephosphorization of the inhibitory p-Tyr site for DNA damage response (26).…”
Section: Discussionmentioning
confidence: 99%
“…PTPN11 is frequently altered in Noonan and Leopard syndromes and cancer cells (Zhang et al, 2015). Analyses of the D61G mutation, frequent in RASopathies, showed that it is gain-function-change, activating the proto-oncogene SRC tyrosine kinase, that in turn activates the serine/threonine kinases PLK1 inducing chromosomal instability and disruption of mitosis (Liu et al, 2016). Among the 20 mutation sites in melanoma, seven are shared with Noonan and Leopard syndromes (F71L, Y279C, A461T, T468M, P491L, Q506P, Q510H).…”
Section: Comparisons Of Specific Genesmentioning
confidence: 99%